High-frequency low-dielectric-loss positive photosensitive polyimide resin glue solution and preparation method
Patent Information
- Application Number
- CN202611393542.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-27
AI Technical Summary
然而,上述体系均无法满足先进封装中多层金属线路互连介质的严苛需求,主要缺陷包括:无法采用紫外线曝光的光刻制图工艺制作多层精细金属线路,无法满足WLP/PLP等对低损耗、高精度图形化及高可靠性的使用要求
1、本发明通过在第一含酚羟基聚酰胺酸酯的主链结构中引入具有不同链长度的含酯基脂肪链段或含酯基芳环链段,以降低树脂的高频下介电常数及介电损耗,同时增加树脂柔顺性,并保持足够的耐热性;然后,将第一含酚羟基聚酰胺酸酯与第二含酚羟基聚酰胺树脂通过复配形成复合树脂体系,利用聚酰胺酸酯主链结构中含酯基脂肪链段或含酯基芳环链段的低介电损耗性与酚羟基的碱性水溶性的协同作用,有效解决了正性光敏树脂的高频低介损性与高光刻工艺性及高抗化性等相互制约的难题,实现了高频低介损性、高光刻分辨率、高铜面粘结性及优良综合力学性能的协同技术效果,可满足硅晶圆封装(WLP)和玻璃面板级封装(PLP)的多层金属布线(RDL)制作工艺要求。
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a high-frequency, low-dielectric-loss positive photosensitive polyimide resin liquid and its preparation method. Background Technology
[0002] In recent years, with the rapid development of the high-frequency signal transmission era represented by 5G mobile phones, emerging industries such as artificial intelligence, autonomous driving, the Internet of Things, intelligent manufacturing, intelligent healthcare, and intelligent monitoring have emerged. High-frequency signal transmission is characterized by high frequency, short wavelength, poor diffraction capability, and rapid signal attenuation. As the size of high-frequency integrated circuits continues to shrink, parasitic resistance and capacitance effects within the circuits become increasingly severe. In particular, the resistance and capacitance delays of multilayer metal interconnect circuits increase by a near-square magnitude, leading to signal transmission delay and crosstalk, which affects circuit performance. To reduce signal transmission delay and crosstalk, as well as the increased power consumption caused by dielectric loss, and to achieve high-speed signal transmission, the interlayer dielectric insulating material of the multilayer metal interconnect structure in radio frequency circuit manufacturing and packaging must have characteristics such as lower dielectric constant and dielectric loss.
[0003] Photosensitive polyimide (PSPI) resin is an important interlayer dielectric insulating material, widely used in high-density integrated circuit manufacturing and advanced packaging, including wafer-level packaging (WLP), panel-level packaging, and 2.5D / 3.0D three-dimensional packaging. PSPI materials mainly include negative PSPI (n-PSPI) and positive PSPI (p-PSPI); based on curing temperature, they are further divided into high-temperature curing (300℃) and low-temperature curing (≤230℃), with low-temperature curing positive PSPI becoming a popular RDL material for WLP and PLP. However, compared to low-temperature curing negative PSPI materials, low-temperature curing positive PSPI materials still have significant shortcomings in terms of resistance to damp heat, chemical immersion, and stress reduction, requiring further improvement to meet the demands of advanced packaging. Currently, polyimide resin films formed by photolithography and high-temperature curing of PSPI resin have a high dielectric constant (3.2, 1 GH). Z ) and high dielectric loss (0.008, 10 GH) Z This makes it impossible to meet the requirements of high-frequency, high-speed integrated circuit manufacturing and packaging. Therefore, developing positive photosensitive polyimide resins with high-frequency, low-diloss characteristics (≤0.005, 10GHz) and their preparation methods has become a key challenge.
[0004] Patent application (CN116655911A) discloses a high-frequency, low-dielectric-loss poly(aryl ester imide) film, which is prepared by chemical imidization of a polyamic acid resin solution obtained by polycondensation of aryl ester-containing tetracarboxylic dianhydride (or a mixture of other tetracarboxylic dianhydrides) and aromatic diamine. The resulting film exhibits a dielectric loss as low as 0.0019–0.0035 at 10 GHz–60 GHz, a moisture absorption rate of only 0.18%–0.53%, and possesses excellent mechanical properties (tensile modulus ≥3.0 GPa, strength ≥100 MPa) and heat resistance (Tg ≥220℃), making it suitable for applications such as high-frequency flexible circuit boards and radio frequency substrates. However, this system is a non-photosensitive polyamic acid resin solution and lacks photolithography capabilities, making it difficult to meet the requirements of fine circuit patterning processes.
[0005] US patents US10,545,406B2 and US8,461,699B2 disclose positive photosensitive resin systems. The former is based on a phenolic hydroxyl-containing polyamide resin, which, after high-temperature curing, has a cyclization degree of less than 10%, exhibiting high elongation, low internal stress, and excellent metal adhesion. The latter is composed of alkali-soluble phenolic hydroxyl-containing resins (such as phenolic resins, polyhydroxyamides, etc.), photoacid-generating agents, and thermo-crosslinking agents, possessing good alkaline water developability and resolution, and excellent pattern adhesion and thermal shock resistance after curing. However, neither of these systems can meet the stringent requirements of multilayer metal circuit interconnect media in advanced packaging. The main drawbacks include: the inability to use ultraviolet light exposure photolithography to fabricate multilayer fine metal circuits, and the inability to meet the requirements of WLP / PLP for low loss, high-precision patterning, and high reliability. Summary of the Invention
[0006] This invention provides a positive photosensitive polyimide resin liquid with high frequency and low dielectric loss characteristics and its preparation method.
[0007] To address the need for low-temperature curing positive photosensitive resins with high frequency and low dielectric loss in advanced packaging technologies such as WLP and PLP, this invention introduces ester-containing aliphatic segments or ester-containing aromatic ring segments with different chain lengths into the main chain structure of a first phenolic hydroxyl-containing polyamide ester. This reduces the dielectric constant and dielectric loss of the resin at high frequencies, while increasing resin flexibility and maintaining sufficient heat resistance. Then, the first and second phenolic hydroxyl-containing polyamide esters are compounded to form a composite resin system. Utilizing the synergistic effect of the low dielectric loss of the ester-containing aliphatic or aromatic ring segments in the polyamide ester main chain structure and the alkaline water solubility of the phenolic hydroxyl groups, this effectively solves the problem of the mutual constraints between high frequency and low dielectric loss, high photolithography processability, and high chemical resistance in positive photosensitive resins. This achieves a synergistic effect of high frequency and low dielectric loss, high photolithography resolution, high copper adhesion, and excellent comprehensive mechanical properties, meeting the multilayer metal wiring (RDL) fabrication process requirements for silicon wafer-level packaging (WLP) and glass panel-level packaging (PLP). To achieve the above objectives, the technical solution of the present invention is as follows.
[0008] This invention provides a positive photosensitive polyimide resin adhesive, which is obtained by mixing the following components: 100 parts of polyaminate resin, 3 to 40 parts of photoacid-generating agent, 3 to 40 parts of thermal crosslinking agent, 0.1 to 20 parts of thermal acid-generating agent, 3 to 40 parts of sensitizer, 3 to 40 parts of tackifier, and an organic solvent; the solid content of the positive photosensitive polyimide resin adhesive is 15 wt.% to 45 wt.%, and the viscosity at room temperature is 500 mPa·s to 4000 mPa·s; wherein, the polyaminate resin is obtained by mixing a first phenolic hydroxyl-containing polyaminate resin and a second phenolic hydroxyl-containing polyaminate resin; the first phenolic hydroxyl-containing polyaminate resin accounts for 50% to 99% of the mass percentage of the polyaminate resin; the main chain structure of the first phenolic hydroxyl-containing polyaminate resin includes ester aliphatic segments or ester aromatic ring segments. The main chain structure of the second phenolic hydroxyl-containing polyaminate resin includes phenyl ether segments.
[0009] The general structural formula of the first phenolic hydroxyl polyamide ester resin is as follows: Where m = 2 to 50.
[0010] X1 is selected from one of the following structural formulas: Where n = 1 to 3.
[0011] Y1 is selected from one of the following structural formulas: .
[0012] R1 is a straight-chain alkane containing C1 to C8 atoms; E1 is a capping group.
[0013] The general structural formula of the second phenolic hydroxyl polyamide ester resin is as follows: Where m' = 2 to 50.
[0014] X2 is selected from one of the following general structural formulas: .
[0015] Y2 is selected from one of the following general structural formulas: .
[0016] R2 is a straight-chain alkane containing C1 to C8 atoms; E2 is a capping group. * indicates a linking site.
[0017] Preferably, the first phenolic hydroxyl polyamic acid ester resin is prepared by the following method: An esterification reaction is carried out between a first aromatic dianhydride containing an ester-based aliphatic or aromatic ring and a first fatty alcohol in a reaction solvent to generate a first aromatic diacid diester. The first aromatic diacid diester is then subjected to acyl chloride reaction with thionyl chloride to generate a first aromatic diester diacyl chloride. The first aromatic diester diacyl chloride is then subjected to a polycondensation reaction with a first phenolic hydroxyl-containing aromatic diamine in a reaction solvent. A reactive end-capping agent and a disiloxane-based silane coupling agent are added, and the reaction continues to generate a first phenolic hydroxyl-containing polyamic acid ester resin solution. After precipitation and separation in a poor solvent, the first phenolic hydroxyl-containing polyamic acid ester resin is obtained. The molar ratio of the first aromatic dianhydride, the first fatty alcohol, and thionyl chloride is 1:2–2.1:2–2.1; the molar ratio of the first aromatic dianhydride to the first phenolic hydroxyl-containing aromatic diamine is 1:0.9–1; and the GPC molecular weight of the first phenolic hydroxyl-containing polyamic acid ester resin is 1 × 10⁻⁶. 4 Up to 3×10 4 The first aromatic dianhydride is at least one of ethylene glycol dimethacrylate, butylene glycol dimethacrylate, hexanediol dimethacrylate, resorcinol dimethacrylate, and hydroquinone dimethacrylate.
[0018] In this invention, the first aromatic dianhydride includes ethylene glycol dicambiguity diphthalic anhydride [1,2-Ethylenebis(trimellitate) dianhydride, 1EBTA, mp 167℃~169℃, molecular weight 410.22]; butylene glycol dicambiguity diphthalic anhydride [1,4-Butylenebis(trimellitate) dianhydride, 2BBTA, mp 160℃~162℃, molecular weight 438.44]; hexanediol dicambiguity diphthalic anhydride [1,6-Hexylenebis(trimellitate) dianhydride, 3HBTA, mp 158℃~160℃, molecular weight 466.26]; and resorcinol dicambiguity diphthalic anhydride [1,3-Phenylenebis(trimellitate) dianhydride, 13PBTA, mp 177℃~178℃, molecular weight 458.24]; At least one of the following: trimellitic anhydride hydroquinone ester [1,4-Phenylenebis(trimellitate) dianhydride, 14PBTA, mp 274℃~275℃, molecular weight 458.24].
[0019] Preferably, the second phenolic hydroxyl polyamic acid ester resin is prepared by the following method: The second aromatic dianhydride and the second fatty alcohol are esterified in a reaction solvent to generate a second aromatic diacid diester; the second aromatic diacid diester is then acylchlorinated with thionyl chloride to generate a second aromatic diester diacyl chloride; the second aromatic diester diacyl chloride is then polycondensed with a second phenolic hydroxyl-containing aromatic diamine in a reaction solvent, followed by the addition of a reactive end-capping agent and a disiloxane-based silane coupling agent, and the reaction continues to generate a second phenolic hydroxyl-containing polyamic acid ester resin solution; after precipitation and separation in a poor solvent, the second phenolic hydroxyl-containing polyamic acid ester resin is obtained; the molar ratio of the second aromatic dianhydride, the second fatty alcohol, and thionyl chloride is 1:2–2.1:2–2.1; the molar ratio of the second aromatic dianhydride to the second phenolic hydroxyl-containing aromatic diamine is 1:0.9–1; the molecular weight of the second phenolic hydroxyl-containing polyamic acid ester resin is 1 × 10⁻⁶. 4 Up to 3×10 4 The second aromatic dianhydride is at least one selected from 2,3,2',3'-diphenyl ether tetracarboxylic dianhydride, 2,3',3,4'-diphenyl ether tetracarboxylic dianhydride, and 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride. In this invention, the second aromatic dianhydride includes at least one selected from 2,3,2',3'-diphenyl ether tetracarboxylic dianhydride (23ODPA), 2,3',3,4'-diphenyl ether tetracarboxylic dianhydride (34ODPA), and 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (44ODPA).
[0020] Preferably, the first phenolic hydroxyl-containing aromatic diamine and the second phenolic hydroxyl-containing aromatic diamine are each independently selected from at least one of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2-bis(4-amino-3-hydroxyphenyl)hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)propane, bis(4-amino-3-hydroxyphenyl)methane, 2,2'-bis[N-(3-aminobenzoamido)-3-amino-4-hydroxyphenyl]hexafluoropropane, 2,2'-bis[N-(4-aminobenzoamide)-3-amino-4-hydroxyphenyl]hexafluoropropane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 1,3-bis(3-aminopropyl)tetraphenyldisiloxane, 1,3-bis(3-aminophenoxy)tetramethyldisiloxane, and 1,3-bis(4-aminophenoxy)tetramethyldisiloxane.
[0021] Aromatic diamines containing phenolic hydroxyl groups include at least one of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (3HFAP, molecular weight 366.17), 2,2-bis(4-amino-3-hydroxyphenyl)hexafluoropropane (4-HFAP, molecular weight 366.17), 2,2-bis(3-amino-4-hydroxyphenyl)propane (3-BAPP, molecular weight 258.17), bis(4-amino-3-hydroxyphenyl)methane (4BAPP, molecular weight 258.17), 2,2'-bis[N-(3-aminobenzoamide)-3-amino-4-hydroxyphenyl]hexafluoropropane (3HFHA, molecular weight 604.32), and 2,2'-bis[N-(4-aminobenzoamide)-3-amino-4-hydroxyphenyl]hexafluoropropane (4HFHA, molecular weight 604.32).
[0022] The reaction solvent includes at least one of N'N dimethylformamide, N'N dimethylacetamide, N-methyl-ε-caprolactam, N-methylpyrrolidone, γ-butyrolactone, ethyl lactate, 1,3-dimethyl-2-imidazolium ketone, dimethyl sulfoxide, dimethyl sulfone, tetramethylene sulfone, tetramethylurea, phenol, m-cresol, ethyl acetate, butyl acetate, sulfolane, p-cresol, 3-chlorophenol, 4-chlorophenol, tetrahydrofuran, ethyl 3-ethoxypropionate, methyl ethyl ketone, cyclopentanone, and cyclohexanone.
[0023] The reactive end-capping agents include at least one of maleic anhydride, 4-aminobenzocyclobutene, 4-vinylaniline, norbornene, allylamine, 4-ethynylphthalic anhydride, 4-phenylethynylphthalic anhydride, 4-ethynylaniline, 3-ethynylaniline, 3-phenylethynylaniline, 4-phenylethynylaniline, 4-(4-aminophenylethynyl)phenylethynyl, 4-[(trimethylsilyl)-ethynyl]aniline, 4-(4-amino-phenyl)-2-methyl-but-3-yn-2-ol, (E)-3-aminocinnamic acid, and propargylamine.
[0024] The disiloxane-based silane coupling agent is at least one selected from 1,3-bis(3-aminopropyl)tetramethyldisiloxane (4MSiNA), 1,3-bis(3-aminopropyl)tetraphenyldisiloxane (4BSiNA), 1,3-bis(3-aminophenoxy)tetramethyldisiloxane (3M2SiA), and 1,3-bis(4-aminophenoxy)tetramethyldisiloxane (4MSiA). Unsuitable solvents include at least one selected from deionized water, methanol, ethanol, hexane, butyl cellosolve, and toluene. In this invention, the addition of the disiloxane-based silane coupling agent is mainly used to improve the interfacial adhesion between the resin and metals such as copper.
[0025] Photoacid-producing agents include diazonoquinone compounds, iodonium salts, and sulfonium salts.
[0026] Considering the effects of inhibiting the solubility of the resin film in the unexposed area and the high solubility of the resin film in the exposed area, diazonaquinone compounds are preferred. These include compounds generated by esterification of diazonaquinone sulfonic acid and polyhydroxy compounds; compounds generated by sulfonation of diazonaquinone sulfonic acid and polyamine compounds; and compounds generated by esterification and / or sulfonation of diazonaquinone sulfonic acid and polyhydroxy polyamine compounds. The proportion of diazonaquinone sulfonic acid substituted in the polyhydroxy polyamine compounds is 30%–90%, preferably 50%–90%. The diazonaquinone compounds include 1,2-diazonaphthoquinone-5-sulfonyl compounds and 1,2-diazonaphthoquinone-4-sulfonyl compounds, such as 2,3,4-trihydroxybenzophenone-1,2-diazonaphthoquinone-5-sulfonate. The polyhydroxy compounds mentioned above include Bis-Z, BisP-EZ, BisP-AP, TekP-4HBPA, TrisP-HAP, TrisP-PA, TrisP-SA, Tris℃R-PA, Bis℃HP-Z, BisP-MZ, BisP-PZ, BisP-IPZ, Bis℃P-IPZ, BisP-CP, BisRS-2P, BisRS-3P, BisP-℃HP, Methylenetris-FR-CR, BisRS-26X, DmL- MBPC, DmL-MB℃, DmL-℃HP, DmL-PCHP, DmL-PC, DmL-PTBP, DmL-34X, DmL-EP, DmL-POP, Dimethylol-Bis℃-P, DmL-PFP, DmL -PSBP, DmL-MTrisPC, TrimL-P, TrimL-35XL, TmL-BP, TmL-HQ, TmL-PP-BPF, TmL-BPA, TMOM-BP, HmL-TPPHBA, HmL-TPHAP (The above are trade names, available from Honshu Chemical Industry Co., Ltd.) BIR-℃, BIP-PC, BIR-PC, BIR-PTBP, BIR-PCHP, BIP-BI℃-F, 4PC, BIR-BIPC-F, TEP-BIP-A, 46DM℃, 46DMOEP, TM-BIP-A (the above are trade names, products of Asahi Organic Materials Co., Ltd.), 2,6-dimethoxymethyl-4-tert-butylphenol, 2,6-dimethoxymethyl-p-cresol, 2,6-diacetoxymethyl-p-cresol, naphthol, 2,3,4-trihydroxybenzophenone, 2,3,4,4'-tetrahydroxybenzophenone, methyl gallate, bisphenol A, bisphenol E, methylene bisphenol, pyrogallol acetone resin, m-cresol resin and phenolic resin.
[0027] Iodotonium salts include bis(4-tert-butylphenyl)iodotonium hexafluorophosphate, diphenyliodotonium hexafluoroarsenate, diphenyliodotonium hexafluorophosphate, 4-isopropyl-4'-methyldiphenyliodotonium tetra(pentafluorophenyl)borate, diphenyliodotonium trifluoromethanesulfonate, diphenyliodonitrate, [4-(trifluoromethyl)phenyl](2,4,6-trimethylphenyl)iodotonium trifluoromethanesulfonate, and [3-(trifluoromethyl)phenyl](2,4,6-trimethylphenyl)iodotonium trifluoromethanesulfonate. (4-Trifluoromethyl)phenyl iodonium trifluoromethanesulfonate, [(4-trifluoromethyl)phenyl](2,4,6-trimethoxyphenyl)iodonium p-toluenesulfonate, phenyl(2,4,6-trimethoxyphenyl)iodonium p-toluenesulfonate, phenyl[3-(trifluoromethyl)phenyl]iodonium trifluoromethanesulfonate, (4-nitrophenyl)(phenyl)iodonium trifluoromethanesulfonate, (4-tolyl)(2,4,6-trimethylphenyl)iodonium trifluoromethanesulfonate, (3- Tolyl(2,4,6-trimethylphenyl)iodonium trifluoromethanesulfonate, (2-tolyl(2,4,6-trimethylphenyl)iodonium trifluoromethanesulfonate, 4-isopropyl-4'-methyldiphenyliodonium tetra(pentafluorophenyl)borate, [4-[(2-hydroxytetradecyl)oxy]phenyl]phenyliodohexafluoroantimonate, (5-fluoro-2-nitrophenyl)(2,4,6-trimethoxyphenyl)iodonium p-toluenesulfonate, diphenyliodonium At least one of the following: hexafluorophosphate, diphenyliodonium hexafluoroarsenate, (3,5-dichlorophenyl)(2,4,6-trimethoxyphenyl)iodonium p-toluenesulfonate, (3-bromophenyl)(trimethylmethyl)iodonium trifluoromethanesulfonate, [4-(bromomethyl)phenyl](2,4,6-trimethoxyphenyl)iodonium p-toluenesulfonate, bis(2,4,6-trimethylpyridine)iodonium hexafluorophosphate, and 4,4'-dimethylyliodonium hexafluorophosphate.
[0028] Sulfonium salts include at least one of 1,3-benzodithiopyrrole tetrafluoroborate, cyclopropyl diphenylsulfonium tetrafluoroborate, dimethyl(methylthio)sulfonium tetrafluoroborate, diphenyl(methyl)sulfonium tetrafluoroborate, (difluoromethyl)bis(2,5-dimethylphenyl)sulfonium tetrafluoroborate, 2-[4-(3-ethoxy-2-hydroxypropoxy)phenylcarbamoyl]ethyldimethylthio-p-toluenesulfonate, 4-hydroxyphenyldimethylsulfonium methanesulfonate, triphenylsulfonium tetrafluoroborate, tris(4-tolyl)sulfonium hexafluorophosphate, tris(4-tolyl)sulfonium trifluoromethanesulfonate, and triethylsulfonium bis(trifluoromethylsulfonyl)imide.
[0029] Thermal crosslinking agents refer to compounds that can undergo crosslinking reactions under heating conditions or under the action of Lewis acids, including compounds containing epoxy groups, compounds containing hydroxymethyl or alkoxymethyl groups, etc.
[0030] Compounds containing epoxy groups include any one of bisphenol A type epoxy resin, bisphenol F type epoxy resin, propylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, polymethyl (glycidyloxypropyl), and epoxy-containing organosilicon, more preferably 3,3'-[oxybis(methylene)]bis[3-ethyl]oxetane, 1,4-butanediol diglycidyl ether, 2,2-bis(4-epoxypropoxyphenyl)propane, 9,9-bis(4-epoxypropyloxy-3-tolyl)fluorene, 9,9-bis(4-epoxypropoxyphenyl)fluorene, 1,3-bis[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]-1,1,3,3-tetramethyldisiloxane, and 1,2-cyclohexanedicarboxylic acid diglycidyl ester. 1,2,7,8-Diepoxyoctane, 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester, triglycidyl isocyanurate, 4,4'-methylenebis(N,N-dicyclopropoxyaniline), neopentyl glycol diglycidyl ether, 2,2'-(2,2,3,3,4,4,5,5-octafluorohexane-1,6-diyl)bis(ethylene oxide), pentaerythritol diglycidyl ether, vinylcyclohexene diglycidyl ether, polyethylene glycol diglycidyl ether (degree of polymerization 1–15), polypropylene glycol diglycidyl ether (degree of polymerization 1–15), polydimethylsiloxane diglycidyl ether (degree of polymerization 1–15), butanediol diglycidyl ether, diglycidyl aniline, trimethylolpropane triglycidyl ether, glycerol triglycidyl Ethers, 5,5-dimethyl-1,3-di(epoxyethylenemethyl)imidazolidine-2,4-dione, 2,2',2''-[methimide-tris(phenoxymethylene)]tri(epoxyethylene), 1,1,1-tris(4-hydroxyphenyl)ethyl triglycidyl ether, bis(2,3-epoxycyclopentyl) ether, 3,4-epoxy-6-methylcyclohexylcarboxylic acid-3',4'-epoxy-6'-methylcyclohexylmethyl ester, vinylcyclohexene epoxy compounds, 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexylmethyl ester, diisoprene diepoxide compounds, tetraphenylglycidyl ether ethane, triphenylglycidyl ether methane, triglycidyl-p-aminophenol, triglycidyl triisocyanate, tetra Glycidyl diaminodiphenylmethane, tetraglycidyl dimethyl diamine, or tetraglycidyl-1,3-diaminomethylcyclohexane; products with trade names may include at least one of HP-850, HP-4032, HP-7200, HP-820, HP-4700, EXA-4710, HP-4770, EXA-859CRP, EXA-1514, EXA-4880, EXA-4850-150, EXA-4850-1000, EXA-4816, EXA-4822, BEO-60E, BPO-20E, HBE-100, DME-100, NC-3000, and NC-6000 (Nippon Kayaku Co., Ltd.).
[0031] Compounds containing hydroxymethyl or alkoxymethyl groups include 46DM℃, 46DMOEP (trade names, manufactured by Asahi Organic Materials Co., Ltd.), DmL-PC, DmL-PEP, DmL-℃, DmL-OEP, DmL-34X, DmL-PTBP, DmL-PCHP, DmL-℃HP, DmL-PFP, DmL-PSBP, DmL-POP, DmL-MB℃, DmLMBPC, DmL-MTrisPC, DmL-Bis℃-Z, DmL-Bis℃HP-Z, DmL-BPC, DmLBis℃-P, DMOM-PC, DMOMPTBP, DMOM-MBPC, TrimL-P, TrimL-35XL, TmL-HQ, TmL-BP, TmL- At least one of the following: pp-BPF, TmL-BPE, TmL-BPA, TmL-BPAF, TmL-BPAP, TMOM-BP, TMOM-BPE, TMOM-BPA, TMOM-BPAF, TMOM-BPAP, HmL-TPPHBA, HmL-TPHAP, HMOM-TPPHBA, HMOM-TPHAP (the above are trade names, available from Honshu Chemical Industry Co., Ltd.), "NIKALAC" MX-290, "NIKALAC" MX-280, "NIKALAC" MX-270, "NIKALAC" MX-279, "NIKALAC" MW-100LM, and "NIKALAC" MX-750LM (Sanwa Chemical Co., Ltd.).
[0032] Thermally induced acid-producing agents refer to compounds that can produce strong acids upon heating, with a thermal decomposition initiation temperature of 150℃-250℃. Examples include alkyl sulfonic acids, perfluoroalkyl sulfonic acids or pyridinium salts of alkyl sulfonic acids, alkylpyridinium salts, diaryl iodine salts, di(alkylaryl)iodine salts, trialkyl sulfonium salts, dialkyl monoaryl sulfonium salts or diaryl monoalkyl iodine salts or ester compounds, including at least one of p-toluenesulfonic acid pyridinium salt, di(tert-butylphenyl)iodine salt of p-toluenesulfonic acid, trimethyl sulfonium salt of trifluorobenzenesulfonic acid, diphenylmethyl sulfonium salt of trifluoromethanesulfonic acid, and p-toluenesulfonic acid-2-methoxyethyl ester.
[0033] Sensitizers include compounds containing phenolic hydroxyl, hydroxyl, or carboxyl groups, which can increase the solubility of the exposed portion in the developer, improve photosensitivity, and shorten development time. The compounds containing phenolic hydroxyl groups include Bis-Z, BisP-EZ, TekP-4HBPA, TrisP-HAP, TrisP-PA, Bis℃HP-Z, BisP-MZ, BisP-PZ, BisP-IPZ, Bis℃P-IPZ, BisP-CP, BisRS-2P, BisRS-3P, BisP-℃HP, methylenetris-FR-CR, BisRS-26X (trade names, available from Honshu Chemical Industry Co., Ltd.), BIP-PC, BIR-PC, BIR-PTBP, and BIR-BI. PC-F (trade name, obtained by Asahi Organic Materials Co., Ltd.), at least one of the following: 2,2-bis(4-hydroxyphenyl)propane, 4,4'-dihydroxydiphenyl sulfone, 2,2-bis(4-hydroxyphenyl)hexafluoropropane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 9,9-bis(4-hydroxyphenyl)fluorene, 4,4'-dihydroxydiphenylcyclohexane, 1,4-naphthodiol, 1,5-naphthodiol, 1,6-naphthodiol, 1,7-naphthodiol, 2,3-naphthodiol, 2,7-naphthodiol, 2,6-naphthodiol, bis(4-hydroxyphenyl) sulfide, and spiro[fluorene-9,9'-xanthon]-3,6'-diol.
[0034] Organic compounds containing hydroxyl groups refer to saturated or unsaturated fatty alcohols containing 2 to 16 carbons, including ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, pentanol, n-hexanol, cyclopropylmethanol, cyclohexylmethanol, 4-methyl-1-cyclohexylmethanol, 3,4-dimethylcyclohexanol, 4-ethylcyclohexanol, 4-tert-butylcyclohexanol, heptanol, octanol, cyclooctanol, 1-cyclohexyl-1-pentanol, and 3,5,5-trimethylcyclohexanol. At least one of the following: alcohol, norbornene-2-methanol, cis-4-hepten-1-ol, cis-3-octen-1-ol, 2,7-octadienol, 2,4,4-methyl-2-pentanol, cyclohexylmethanol, cis-2-hexen-1-ol, n-hexanol, 1-hexadecyl alcohol, 2-ethyl-1-butanol, DL-2-methyl-1-butanol, isoamyl alcohol, 3-methyl-2-butanol, 4-methyl-2-pentanol, isobutanol, and neopentanol.
[0035] Organic compounds containing carboxyl groups refer to carboxylic acid compounds with 2 to 16 carbon atoms, including at least one of acetic acid, propionic acid, butyric acid, valeric acid, 2-methyl-4-pentenoic acid, 4-methyl-2-pentenoic acid, 2-methyl-2-pentenoic acid, 3-methyl-n-pentanoic acid, 4-methyln-pentanoic acid, 2-ethylbutyric acid, heptanoic acid, octanoic acid, n-nonanoic acid, isononanoic acid, n-decanoic acid, 2-heptenoic acid, 2-octenoic acid, 2-nonenoic acid, 2-decenoic acid, 10-undecenoic acid, p-methoxybenzoic acid, m-methylbenzoic acid, benzoic acid, mandelic acid, trans-2-hexenoic acid, 3,7-dimethyl-6-octanoic acid, sorbic acid, 3,5,5-trimethylhexanoic acid, lauric acid, and myrcenoic acid.
[0036] Organic solvents refer to compounds that can dissolve components to form homogeneous solutions, including at least one of N-methylpyrrolidone, N,N'-dimethylacetamide, N,N'-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, ethyl acetate, butyl acetate, n-propyl acetate, methyl lactate, ethyl lactate, propyl lactate, butyl lactate, toluene, xylene, mesitylene, diacetone alcohol, methyl isobutyl ketone, cyclopentanone, cyclohexanone, methyl ethyl ketone, methyl propyl ketone, tetrahydrofuran, tetrahydropyran, dioxane, dioxane, ethylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monomethyl ether acetate.
[0037] Tackifiers include γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidyl ether oxypropyltrimethoxysilane, γ-glycidyl ether oxypropyltriethoxysilane, 3-methacryloyloxypropyldimethoxymethylsilane, 3-methacryloyloxypropyltrimethoxysilane, 3-ureidopropyltrimethoxysilane, 3-ureidopropyltriethoxysilane, 2-cyanoethyltrimethoxysilane, 2-cyanoethyltriethoxysilane, 3-isocyanate-based trimethoxysilane, 3-isocyanate-based triethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptomethyltrimethoxysilane, 3 At least one of the following: mercaptomethyldimethoxysilane, 3-mercaptopropylethoxydimethoxysilane, 3-mercaptopropyltripropoxysilane, vinyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-(triethoxysilyl)propylsuccinic anhydride, 3-(m-aminophenoxy)trimethoxysilane, p-aminophenyltrimethoxysilane, aminophenyltrimethoxysilane, vinylmethyldiethoxysilane, vinyltriethoxysilane, 3-acetoxypropyltrimethoxysilane, 3-methacryloyloxypropyltriethoxysilane, 3-acryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, and 3-piperazinylpropylmethyldimethoxysilane.
[0038] This invention provides a method for preparing a positive photosensitive polyimide resin adhesive with high-frequency and low dielectric loss characteristics: In a Class 1000 cleanroom equipped with a yellow light source, 100 parts by weight of hydroxyl-containing polyamide resin (A), 3-40 parts by weight of photoacid-generating agent (B), 3-40 parts by weight of thermal crosslinking agent (C), 0.1-20 parts by weight of thermal acid-generating agent (D), 3-40 parts by weight of sensitizer (E), and 3-40 parts by weight of tackifier (G) are added in batches to an organic solvent (F) under stirring to form a homogeneous solution. After filtration and dispensing, a positive photosensitive polyimide resin adhesive is obtained, with a solid content of 15-45 wt.% and a solution viscosity of 500-4000 mPa·s at room temperature.
[0039] This invention provides an application of the aforementioned positive photosensitive polyimide resin solution in preparing a dielectric insulating layer film for multilayer metal interconnect circuits on a substrate surface. The substrate is a silicon wafer or a glass substrate.
[0040] The positive photosensitive polyimide resin liquid with high-frequency and low dielectric loss characteristics provided by this invention is suitable not only for 12-inch silicon wafer surfaces but also for fabricating dielectric insulating films for multilayer metal interconnect circuits (RDLs) on large-area (600mm x 600mm) glass substrate surfaces. Its photolithography patterning process includes: coating: forming a uniformly thick liquid film by spin-coating the positive photosensitive polyimide resin liquid onto the wafer surface or by inkjet printing onto a large-area glass substrate surface; pre-baking: performing pre-baking treatment at 80℃~150℃ to form a semi-solid film; exposure: performing exposure treatment using an ultraviolet light source through a photomask or photomask; development and rinsing: using an aqueous developer (2.38%). TMAH) is developed by spraying or immersion, and then rinsed with ultrapure water to form a three-dimensional pattern; heat curing: the precursor resin three-dimensional pattern on the substrate surface is heated and cured to transform it into a high heat-resistant curable resin three-dimensional pattern; through electroplating copper process, a continuous conductive copper layer is formed on the surface of the resin three-dimensional pattern; then, through photolithography patterning process, the continuous conductive copper layer is etched to form conductive copper lines, completing one RDL process (1P1M); repeat the above process to form a second RDL process (2P2M) on its surface; continue to repeat the above process to form a third RDL process (3P3M).
[0041] The beneficial effects of this invention are: 1. This invention introduces ester-containing aliphatic segments or ester-containing aromatic ring segments with different chain lengths into the main chain structure of a first phenolic hydroxyl polyamide ester to reduce the dielectric constant and dielectric loss of the resin at high frequencies, while increasing the resin's flexibility and maintaining sufficient heat resistance. Then, the first phenolic hydroxyl polyamide ester and the second phenolic hydroxyl polyamide resin are compounded to form a composite resin system. By utilizing the synergistic effect of the low dielectric loss of the ester-containing aliphatic segments or ester-containing aromatic ring segments in the polyamide ester main chain structure and the alkaline water solubility of the phenolic hydroxyl groups, the problem of mutual constraints between high frequency low dielectric loss, high photolithography processability, and high chemical resistance of positive photosensitive resins is effectively solved. This invention achieves a synergistic technical effect of high frequency low dielectric loss, high photolithography resolution, high copper surface adhesion, and excellent comprehensive mechanical properties, which can meet the multilayer metal wiring (RDL) fabrication process requirements of silicon wafer packaging (WLP) and glass panel-level packaging (PLP).
[0042] 2. The positive photosensitive polyimide resin liquid of the present invention has high photolithographic resolution and excellent photolithographic processability. The liquid film formed by coating can form a high-quality three-dimensional photolithographic pattern after pre-baking, exposure, development, rinsing and heat curing (180℃~230℃). The resin film formed after heat curing has the characteristics of high frequency and low dielectric loss, high resistance to damp heat, high resistance to chemical immersion, and high copper surface adhesion. It is suitable for multilayer metal interconnect wiring in high-density integrated circuit advanced packaging.
[0043] 3. The positive PSPI resin solution described in this invention has excellent photolithography processability. A liquid film with uniform thickness is formed on the surface of a 12-inch silicon wafer through spin coating. The resin three-dimensional pattern formed after photolithography processes such as pre-baking, exposure, and development has the characteristics of high resolution and controllable steepness. The resin film formed after low-temperature curing (≤230℃) not only has the characteristics of low dielectric constant (≤3.20, 10GHz) and dielectric loss (≤0.0050, 10GHz), but also has excellent comprehensive mechanical properties, resistance to damp heat, resistance to chemical corrosion and copper surface adhesion. It is suitable for fabricating interlayer dielectric insulating films for multilayer metal interconnect structures of high-frequency integrated circuits. Detailed Implementation
[0044] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.
[0045] A positive photosensitive polyimide resin solution with high-frequency and low dielectric loss characteristics, its preparation method, and its applications are disclosed. The positive photosensitive polyimide resin solution can form a uniformly thick liquid film on the surface of a 12-inch silicon wafer through a spin-coating process. The stereolithographic resin pattern formed after pre-baking, ultraviolet exposure, and aqueous development exhibits excellent photolithographic processability. The resin film formed after low-temperature curing (180℃~230℃) possesses characteristics such as high-frequency and low dielectric loss, high resistance to damp heat, high resistance to chemical etching, and high copper adhesion, making it suitable for manufacturing multilayer metal interconnect circuit layers for advanced packaging such as high-density integrated circuit wafer-level packaging. The positive photosensitive polyimide resin solution is composed of a phenolic hydroxyl polyamide ester mixed resin, a photoacid-generating agent, a thermotropic crosslinking agent, and a solvent, wherein the phenolic hydroxyl polyamide ester mixed resin includes a first phenolic hydroxyl polyamide ester and a second phenolic hydroxyl polyamide resin. The first phenolic hydroxyl polyamide ester is formed by polycondensation reaction of an aromatic diester diacyl chloride containing ester aliphatic or aromatic ring segments and a phenolic hydroxyl aromatic diamine and a reactive end-capping agent; the second phenolic hydroxyl polyamide resin is formed by polycondensation reaction of a diphenyl ether type diester diacyl chloride and a phenolic hydroxyl aromatic diamine and a reactive end-capping agent.
[0046] The following evaluation method was used to evaluate the performance of the positive photosensitive resin liquid of the present invention.
[0047] 1. Photolithography process evaluation method: Positive photosensitive resin liquid is uniformly coated onto the surface of a 12-inch silicon wafer or a large-area glass substrate using a spin coating process to form a liquid film of uniform thickness. After baking at 100℃~110℃ for 1min~3min, a mask is placed on the surface and exposed with ultraviolet lamps (i-line and g-line). Aqueous developer (2.38wt% TMAH) is used for development by spraying or immersion. After rinsing with ultrapure water, it is heated and cured in a nitrogen-protected forced-air oven. Specifically, it is heated and cured at 150℃ for 1h, 200℃ for 1h, and 230℃ for 1h to obtain a cured resin stereolithography pattern with a thickness of 8.0µm.
[0048] The photolithography processability is evaluated by observing the 3D pattern under an optical microscope: If the thickness uniformity of the cured resin film after curing is ≤0.50%, the resolution of the photolithographic pattern (strip patterns and through-holes) is ≤5.0µm, and the patterns are cleanly developed without any foreign matter residue, the photolithography processability is rated as "Excellent". If the thickness uniformity of the cured resin film after curing is 0.51%~0.99%, the resolution of the photolithographic pattern is ≤10.0µm, and the patterns are cleanly developed without any foreign matter residue, the photolithography resolution is rated as "Good". If the thickness uniformity of the cured resin film after curing is ≥1.0%, the resolution of the pattern is ≥15µm, and the patterns are not cleanly developed with foreign matter residue, the photolithography resolution is rated as "Poor".
[0049] 2. High-Frequency Low Dielectric Loss Evaluation Method: The polyimide film formed after high-temperature curing exhibits high-frequency low dielectric loss characteristics. Testing was performed using a Keysignal N5227B PNA vector network analyzer. The test film sample size was 6.5cm × 5.5cm. After wiping the surface clean with ethanol, it was dried at 90℃ for 30 min. The dielectric loss value was measured at a test frequency of 10GHz and room temperature. The test result is the average of three repeated test results.
[0050] If the dielectric constant of the prepared polyimide film is ≤3.4 and the dielectric loss tangent is ≤0.0050, it is rated as "Excellent". If the dielectric constant of the prepared polyimide film is ≤3.4 and the dielectric loss tangent is between 0.0051 and 0.0099, it is rated as "Good". If the dielectric constant of the prepared polyimide film is ≥3.5 and the dielectric loss tangent is ≥0.0100, it is rated as "Poor".
[0051] 3. Evaluation method for chemical corrosion resistance: The stereolithographic pattern of the resin after heat curing is immersed in a caustic solution (a mixed solution of 1 wt.% potassium hydroxide, 39 wt.% 3-methoxy-3-methyl-1-butanol and 60 wt.% dimethyl sulfoxide (DMSO)) at 100°C for 1 hour. After washing with water and air drying, the chemical corrosion resistance of the cured resin film is evaluated by measuring the film thickness change and observing under an optical microscope: If the thickness change of the cured resin film after immersion is within ±1% and no cracks or defects are produced, it is evaluated as "excellent"; if the thickness change of the cured resin film after immersion is within ±3% and no cracks or defects are produced, it is evaluated as "good"; if the thickness change of the cured resin film after immersion exceeds ±5% or cracks or defects are produced, it is evaluated as "poor".
[0052] 4. Evaluation method for resistance to damp heat: A high-frequency, low-dielectric-loss positive photosensitive resin was spin-coated onto the surface of a 12-inch silicon wafer to form a liquid film. After baking at 120°C for 3 minutes, the surface was exposed to ultraviolet light (i-line and g-line) without a mask. The substrate was then developed by spraying or immersion with an aqueous developer (2.38% TMAH), rinsed with ultrapure water, and cured in a nitrogen-protected oven (150°C for 1 hour, 200°C for 1 hour, and 230°C for 1 hour) to form a cured resin film on the substrate surface. The substrate was then placed in a pressure cooker at 120°C / 2 atm for 100 hours and subjected to three thermal shock cycles from room temperature to 260°C. The longitudinal section of the copper-tin protrusions covered with the resin film was cut using a FIB, and the interface morphology between the copper-tin protrusions and the resin film was observed using an optical microscope. If no cracks or voids are found at the interface between the copper-tin protrusion and the cured resin, it is rated as "Excellent"; if a few cracks or voids are found at the interface between the copper-tin protrusion and the cured resin, it is rated as "Good"; if many cracks or voids are found at the interface between the copper-tin protrusion and the cured resin, it is rated as "Poor".
[0053] 5. Evaluation method for adhesion to copper surface: Positive photosensitive resin solution is spin-coated onto the surface of a 12-inch silicon wafer to form a uniformly thick film; after baking at 100℃~110℃ for 1min~3min, the surface is exposed with ultraviolet lamps (i-line and g-line) without placing a mask; aqueous developer (2.38% TMAH) is used for spray or immersion development, followed by rinsing with ultrapure water, and then heat curing in a nitrogen-protected oven (150℃ for 1h, 200℃ for 1h, 230℃ for 1h) to obtain a cured resin film with a thickness of 8.0µm.
[0054] The adhesion between the film and copper was evaluated using a cross-cut test: "Excellent" was defined as 0 crosses of film peeled off by tape per 100 crosses; "Good" was defined as 1 to 10 crosses of film peeled off by tape per 100 crosses; and "Poor" was defined as more than 11 crosses of film peeled off by tape per 100 crosses.
[0055] 6. Comprehensive performance evaluation method: If all indicators are "excellent", the comprehensive performance evaluation is "excellent"; if one of the indicators is "good", the comprehensive performance evaluation is "good"; if one of the indicators is "poor", the comprehensive performance evaluation is "poor".
[0056] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials and reagents used in the following examples are commercially available. Unless otherwise specified, the reaction temperatures in the following examples were all conducted at room temperature.
[0057] The preparation of the first phenolic hydroxyl polyamide ester resin and the second phenolic hydroxyl polyamide ester resin will be further explained through specific synthesis examples.
[0058] .
[0059] .
[0060] Resin Synthesis Example 1 A method for synthesizing a first phenolic hydroxyl polyamide ester resin includes the following steps: S1. In a 500 mL three-necked round-bottom flask equipped with a mechanical stirrer, thermometer, and nitrogen protection device, add 41.02 g of ethylene glycol trimellitic anhydride (1EBTA, molecular weight 410.22), 9.20 g of ethanol, 15.82 g of pyridine (as a base neutralization reaction carboxylic acid and a promoter for anhydride ring opening), and 129 g of N-methylpyrrolidone (NMP). Stir the reaction at room temperature for 6 h to allow the anhydride of 1EBTA to undergo esterification with ethanol, generating 1,2-ethylene glycol bis(ethylene trimellitic acid monoethyl ester). React the generated 1,2-ethylene glycol bis(ethylene trimellitic acid monoethyl ester) with 23.79 g of SOCl2 at 0℃~5℃ for 2 h, then continue the reaction at room temperature for 4 h to allow the carboxylic acid in 1,2-ethylene glycol bis(ethylene trimellitic acid monoethyl ester) to undergo acyl chloride reaction with thionyl chloride, generating the corresponding 1EBTA diethyl acyl chloride solution. The chemical name of 1EBTA diethyl diacid chloride is 1,2-ethylene glycol bis(triphenyltrihydride) diethyl diacid chloride, which is a diethyl diacid chloride monomer.
[0061] S2. In a 1L three-necked round-bottom flask equipped with a mechanical stirrer, thermometer and nitrogen protection device, add 36.62g of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (3HFAP, molecular weight 366.17, as a dianhydride monomer) and 158g of NMP, and stir to dissolve them to form a homogeneous transparent solution (3HFAP-NMP solution).
[0062] The diethyl diacid chloride solution of 1EBTA prepared in S1 was added dropwise to a 3HFAP-NMP solution over a period of 0.5 h; the reaction was then carried out at room temperature for 10 h; 1.48 g of phthalic anhydride (PA, chemical name: phthalic anhydride, as a capping agent) and 1.00 g of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (4MSiNA, abbreviated as siloxane diamine) were then added, and the mixture was stirred for another 1 h; the reaction solution was poured into 5 L of deionized water, the solid precipitated, filtered, and vacuum dried to obtain primary polyamic acid ester resin (PAE-1-1). The primary polyamic acid ester resin was dissolved in tetrahydrofuran to form a solution, and residual metal or non-metal ions were removed by adsorption with anion exchange resin and cation exchange resin. The solvent was then removed by drying to obtain a high-purity first phenolic hydroxyl-containing polyamic acid ester resin solid (abbreviated as PAE1-1-1: 1EBTA-3HFAP).
[0063] Resin Synthesis Example 2 The synthesis method of the first phenolic hydroxyl polyaminate resin was carried out according to the synthesis method of resin synthesis example 1, except that 41.02 g of ethylene glycol dimeritic anhydride (1EBTA, molecular weight 410.22) in resin synthesis example 1 was replaced with 43.85 g of butylene dimeritic anhydride (2BBTA, molecular weight 438.44); all other steps were the same, and a high-purity first phenolic hydroxyl polyaminate resin solid (abbreviated as PAE1-1-2: 2BBTA-3HFAP) was obtained.
[0064] Resin Synthesis Example 3 The synthesis method of the first phenolic hydroxyl polyamate resin was carried out according to the synthesis method of Resin Synthesis Example 1, except that the 41.02g of ethylene glycol dimeritic anhydride (1EBTA, molecular weight 410.22) in Resin Synthesis Example 1 was replaced with 46.63g of hexanediol dimeritic anhydride (3HBTA, molecular weight 466.26); all other steps were the same, and a high-purity first phenolic hydroxyl polyamate resin solid (abbreviated as PAE1-1-3: 3HBTA-3HFAP) was obtained.
[0065] Resin Synthesis Example 4 The first method for synthesizing phenolic hydroxyl polyaminate resin involves replacing 41.02 g of ethylene glycol dimeritic anhydride (1EBTA, molecular weight 410.22) in resin synthesis example 1 with 45.82 g of resorcinol dimeritic anhydride (13PBTA, molecular weight 458.24); all other steps are the same, resulting in a high-purity phenolic hydroxyl polyaminate resin solid (abbreviated as PAE1-1-3: 13PBTA-3HFAP).
[0066] Resin Synthesis Example 5 The synthesis method of the first phenolic hydroxyl polyaminate resin was carried out according to the synthesis method of resin synthesis example 1, except that 41.02g of dipyritin ethylene glycol ester (1EBTA, molecular weight 410.22) in resin synthesis example 1 was replaced with 45.82g of dipyritin hydroquinone ester (14PBTA, molecular weight 458.24); all other steps were the same, and a high-purity first phenolic hydroxyl polyaminate resin solid (abbreviated as PAE1-1-3: 14PBTA-3HFAP) was obtained.
[0067] Resin Synthesis Example 6 The synthesis method of the first phenolic hydroxyl polyaminate resin was carried out according to the synthesis method of Resin Synthesis Example 1, except that 36.62 g of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (3HFAP, molecular weight 366.17, as a dianhydride monomer) in Resin Synthesis Example 1 was replaced with 36.62 g of 2,2-bis(4-amino-3-hydroxyphenyl)hexafluoropropane (4HFAP, molecular weight 366.17); all other steps were the same, and a high-purity first phenolic hydroxyl polyaminate resin solid (abbreviated as PAE1-1-6: 1EBTA-4HFAP) was obtained.
[0068] Resin Synthesis Example 7 The synthesis method of the first phenolic hydroxyl polyaminate resin was carried out according to the synthesis method of Resin Synthesis Example 1, except that 36.62 g of 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (3HFAP, molecular weight 366.17, as a dianhydride monomer) in Resin Synthesis Example 1 was replaced with 60.43 g of 2,2'-bis[N-(3-aminobenzoamide)-3-amino-4-hydroxyphenyl]hexafluoropropane (3HFHA, molecular weight 604.3); all other steps were the same, and a high-purity first phenolic hydroxyl polyaminate resin solid (abbreviated as PAE1-1-7: 1EBTA-3HFHA) was obtained.
[0069] Resin Synthesis Example 8 The synthesis method of the first phenolic hydroxyl polyaminate resin was carried out according to the synthesis method of resin synthesis example 1, except that 36.62 g of 2,2'-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (3HFAP, molecular weight 366.17, as a dianhydride monomer) in resin synthesis example 1 was replaced with 60.43 g of 2,2'-bis[N-(3-aminobenzoamide)-4-amino-3-hydroxyphenyl]hexafluoropropane (abbreviated as 4HFHA, molecular weight 604.32); all other steps were the same, and a high-purity first phenolic hydroxyl polyaminate resin solid (abbreviated as PAE1-1-8:1EBTA-4HFHA) was obtained.
[0070] Resin Synthesis Example 9 The synthesis method of the first phenolic hydroxyl polyaminate resin was carried out according to the synthesis method of resin synthesis example 1, except that 36.62g of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (3HFAP, molecular weight 366.17, as a dianhydride monomer) in resin synthesis example 1 was replaced with 25.82g of 2,2-bis(3-amino-4-hydroxyphenyl)propane (3HHAP, molecular weight 258.17). All other steps were the same, and a high-purity first phenolic hydroxyl polyaminate resin solid (abbreviated as PAE1-1-9:1EBTA-3HHAP) was obtained.
[0071] Resin Synthesis Example 10 The synthesis method of the first phenolic hydroxyl polyaminate resin was carried out according to the synthesis method of Resin Synthesis Example 1, except that 36.62 g of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (3HFAP, molecular weight 366.17, as a dianhydride monomer) in Resin Synthesis Example 1 was replaced with 25.82 g of 2,2-bis(4-amino-3-hydroxyphenyl)propane (4HHAP, molecular weight 258.17); all other steps were the same, and a high-purity first phenolic hydroxyl polyaminate resin solid (abbreviated as PAE1-1-10: 1EBTA-4HHAP) was obtained.
[0072] Table 1. Comparison of raw materials in Examples 1 to 10 Example 1 1EBTA-3HFAP PAE1-1-1 Example 2 2BBTA-3HFAP PAE1-1-2 Example 3 3HBTA-3HFAP PAE1-1-3 Example 4 13PBTA-3HFAP PAE1-1-3 Example 5 14PBTA-3HFAP PAE1-1-3 Example 6 1EBTA-4HFAP PAE1-1-6 Example 7 1EBTA-3HFHA PAE1-1-7 Example 8 1EBTA-4HFHA PAE1-1-8 Example 9 1EBTA-3HHAP PAE1-1-9 Example 10 1EBTA-4HHAP PAE1-1-10 Resin Synthesis Example 11 The second method for synthesizing a phenolic hydroxyl polyamide ester resin includes the following steps: S1. In a 500mL three-necked round-bottom flask equipped with a mechanical stirrer, thermometer, and nitrogen protection device, add 31.02g of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (44ODPA), 9.20g of ethanol, 15.82g of pyridine, and 129g of N-methylpyrrolidone (NMP). Stir the mixture at room temperature for 6 hours to allow 44ODPA to undergo esterification with ethanol, producing the corresponding 3,3'-oxobis(ethyl phthalate). React the generated 3,3'-oxobis(ethyl phthalate) with 23.79g of SOCl2 at 0℃~5℃ for 2 hours, then continue the reaction at room temperature for 4 hours to allow the carboxylic acid in 3,3'-oxobis(ethyl phthalate) to undergo acyl chloride reaction with thionyl chloride, producing a diethyl diacyl chloride solution of 44ODPA, which serves as the diacyl chloride monomer.
[0073] S2. In a 1L three-necked round-bottom flask equipped with a mechanical stirrer, thermometer and nitrogen protection device, add 36.62g of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (3HFAP, molecular weight 366.17) and 158g of NMP, stir to dissolve and form a homogeneous transparent solution (3HFAP-NMP solution).
[0074] The diethyl diacyl chloride solution of 44ODPA prepared in S1 was added dropwise to a 3HFAP-NMP solution over a period of 0.5 h; the reaction was then carried out at room temperature for 10 h; 1.48 g of phthalic anhydride and 1.00 g of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (4MSiNA) were then added, and stirring was continued for 1 h; the reaction solution was poured into 5 L of deionized water, the solid precipitated, filtered, and vacuum dried to obtain the primary polyaminate resin (PAE-2-1). The primary polyaminate resin was dissolved in tetrahydrofuran to form a solution, and residual metal or non-metal ions were removed by adsorption with anion exchange resin and cation exchange resin to obtain a high-purity second phenolic hydroxyl-containing polyaminate resin solid (abbreviated as PAE-2-1: 44ODPA-3HFAP).
[0075] Resin Synthesis Example 12 The second method for synthesizing phenolic hydroxyl polyamide ester resin was carried out according to the method of resin synthesis example 11, except that 31.02 g of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (44ODPA) in resin synthesis example 11 was replaced with 31.02 g of 2,2',3,3'-diphenyl ether tetracarboxylic dianhydride (33ODPA); all other steps were the same, and high-purity phenolic hydroxyl polyamide resin-2 solid (PAE-2-2:33ODPA-3HFAP) was obtained.
[0076] Resin Synthesis Example 13 The second method for synthesizing phenolic hydroxyl polyamide ester resin was carried out according to the method of resin synthesis example 11, except that 31.02 g of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (44ODPA) in resin synthesis example 11 was replaced with 31.02 g of 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride (34ODPA); all other steps were the same, and high-purity phenolic hydroxyl polyamide resin-2 solid (PAE-2-3: 34ODPA-3HFAP) was obtained.
[0077] Resin Synthesis Example 14 The second method for synthesizing phenolic hydroxyl polyamide ester resin was carried out according to the method of resin synthesis example 11, except that 31.02 g of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (44ODPA) in resin synthesis example 11 was replaced with a mixture of 15.51 g of 2,2',3,3'-diphenyl ether tetracarboxylic dianhydride (33ODPA) and 15.51 g of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (44ODPA); all other steps were the same, and high-purity phenolic hydroxyl polyamide resin-2 solid (PAE-2-4: 33ODPA / 44ODPA(1 / 1)-3HFAP) was obtained.
[0078] Resin Synthesis Example 15 The second method for synthesizing phenolic hydroxyl polyamide ester resin was carried out according to the method of resin synthesis example 11, except that 31.02 g of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (44ODPA) in resin synthesis example 11 was replaced with a mixture of 15.51 g of 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride (34ODPA) and 15.51 g of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (44ODPA); all other steps were the same, and high-purity phenolic hydroxyl polyamide resin-2 solid (PAE-2-5: 34ODPA / 44ODPA(1 / 1)-3HFAP) was obtained.
[0079] Resin Synthesis Example 16 The second method for synthesizing phenolic hydroxyl polyamide ester resin was carried out according to the method of resin synthesis example 11, except that 31.02 g of 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (44ODPA) in resin synthesis example 11 was replaced with a mixture of 15.51 g of 2,2',3,3'-diphenyl ether tetracarboxylic dianhydride (33ODPA) and 15.51 g of 2,3,3',4'-diphenyl ether tetracarboxylic dianhydride (34ODPA); all other steps were the same, and high-purity phenolic hydroxyl polyamide resin-2 solid (PAE-2-6: 33ODPA / 34ODPA(1 / 1)-3HFAP) was obtained.
[0080] Table 2 Comparison of raw materials in Examples 11 to 16 Example 11 44ODPA-3HFAP PAE-2-1 Example 12 33ODPA-3HFAP PAE-2-2 Example 13 34ODPA-3HFAP PAE-2-3 Example 14 33ODPA / 44ODPA(1 / 1)-3HFAP PAE-2-4 Example 15 34ODPA / 44ODPA(1 / 1)-3HFAP PAE-2-5 Example 16 33ODPA / 34ODPA(1 / 1)-3HFAP PAE-2-6 Note: (1 / 1) indicates a mass ratio of 1:1.
[0081] The positive photosensitive polyimide resin liquid is further illustrated through specific embodiments.
[0082] Example 1 A method for preparing a positive photosensitive polyimide resin adhesive includes the following steps: In a cleanroom equipped with a yellow light, 50g of the first phenolic hydroxyl polyamide ester resin (PAE-1-1) prepared in Resin Synthesis Example 1 and 50g of the phenolic hydroxyl polyamide resin-2 (PAE-2-1) prepared in Resin Synthesis Example 11 were weighed and dissolved in 100g of γ-butyrolactone solvent to form a homogeneous solution. Then, 10g of 2,3,4-trihydroxybenzophenone-1,2-naphthoquinone-5-sulfonate (photoacid generator), 5.0g of p-toluenesulfonic acid-2-methoxyethyl ester (thermal acid generator), 5.0g of 2,2-bis(4-hydroxyphenyl)propane (sensitizer), 4.0g of 2,2-bis(4-epoxypropoxyphenyl)propane (thermal crosslinking agent), and 5.0g of γ-aminopropyltriethoxysilane (adhesive) were added sequentially and stirred at room temperature for 1h to obtain a positive photosensitive polyimide resin solution. The solid content of the positive photosensitive polyimide resin solution is 35 wt.%, and the viscosity is 1500 mPa.s.
[0083] The positive photosensitive polyimide resin solution of Example 1 was uniformly coated onto the surface of a 12-inch silicon wafer using a spin coating process. After baking at 110°C for 3 minutes, a mask was placed on the surface and exposed using ultraviolet lamps (i-line and g-line). Spray development was performed using an alkaline aqueous solution of tetramethylammonium hydroxide (2.38wt% TMAH). After rinsing with deionized / ultrapure water, the film was cured in a nitrogen-protected forced-air oven. Specifically, the film was cured at 150°C for 1 hour, at 200°C for 1 hour, and at 230°C for 1 hour to obtain a stereolithographic pattern formed by the thermosetting resin film.
[0084] The performance of the positive photosensitive polyimide resin liquid of Example 1 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.85, photolithography resolution is 4.5µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.3, dielectric loss factor is 0.0045, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.86%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0085] Example 2 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 1, except that PAE-1-1 in Example 1 is replaced by PAE-1-2, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid in Example 2 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.88, photolithography resolution is 4.6µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.2, dielectric loss factor is 0.0045, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.77%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0086] Example 3 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 1, except that PAE-1-1 in Example 1 is replaced by PAE-1-3, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid in Example 3 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.90, photolithography resolution is 4.5µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.3, dielectric loss factor is 0.0038, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.68%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0087] Example 4 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 1, except that PAE-1-1 in Example 1 is replaced by PAE-1-4, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid in Example 4 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.87, photolithography resolution is 4.3µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.2, dielectric loss factor is 0.0039, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.74%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0088] Example 5 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 1, except that PAE-1-1 in Example 1 is replaced by PAE-1-5, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Example 5 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.85, photolithography resolution is 7.3µm, rated as "Good"; ② High frequency and low dielectric loss: dielectric constant is 3.3, dielectric loss factor is 0.0037, rated as "Excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.74%, no microcracks or defects were observed, rated as "Excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "Excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "Excellent"; ⑥ Comprehensive performance evaluation: one indicator is good, rated as "Good".
[0089] Comparative Example 1 The preparation method of the positive photosensitive polyimide resin solution is the same as that in Example 1, except that PAE-2-1 in Example 1 is removed, and all other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Comparative Example 1 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.86, photolithography resolution is 4.6µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.4, dielectric loss factor is 0.0070, rated as "good"; ③ Chemical corrosion resistance: film thickness change rate is 0.73%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 8 / 100, rated as "good"; ⑥ Comprehensive performance evaluation: both indicators are good, rated as "good".
[0090] Comparative Example 2 The preparation method of the positive photosensitive polyimide resin solution is the same as that in Example 1, except that PAE-1-1 in Example 1 is removed, and all other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Comparative Example 2 was evaluated using the above performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.86, photolithography resolution is 12.2µm, rated as "poor"; ② High frequency and low dielectric loss: dielectric constant is 3.4, dielectric loss factor is 0.0080, rated as "good"; ③ Chemical corrosion resistance: film thickness change rate is 0.78%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 14 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: one indicator is poor, rated as "poor".
[0091] The solid content of the positive photosensitive polyimide resin adhesives in Examples 1 to 6 and Comparative Examples 1 to 2 was 35 wt.% ± 2.0 wt.%, and the viscosity (23°C) was 1500 mPa.s ± 100 mPa.s.
[0092] By comparing the first phenolic hydroxyl polyaminate resin (PAE-1) series resin (PAE-1) and the second phenolic hydroxyl polyaminate resin (PAE-2-1) in Examples 1 to 6 at a weight ratio of 1:1, the influence of the different molecular structures of the ester-containing aromatic dianhydride monomers on the overall performance of the prepared positive photosensitive resins was investigated.
[0093] The results showed that the positive photosensitive polyimide resin adhesive prepared by thoroughly mixing the mixed resin formed by combining PAE-1-1 or PAE-1-2, PAE-1-3, PAE-1-4 and PAE-2-1 in a 1:1 weight ratio with other components such as photoacid-producing agents, thermal crosslinking agents, and tackifiers exhibited excellent comprehensive performance, and was rated as "excellent". However, the positive photosensitive polyimide resin adhesive prepared by combining the mixed resin formed by combining PAE-1-5 and PAE-2-1 in a 1:1 weight ratio had poor resistance to damp heat, and was rated as "good". In contrast, when the phenolic hydroxyl polyamide ester resin (PAE-1-1) or the phenolic hydroxyl polyamide ester resin (PAE-2-1) was only a single component, rather than a mixture of both, the comprehensive performance of the prepared positive photosensitive polyimide resin adhesive was rated as "good" or "poor".
[0094] Example 6 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 1, except that PAE-1-1 in Example 1 is replaced by PAE-1-6, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Example 6 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.89, photolithography resolution is 4.4µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.2, dielectric loss factor is 0.0046, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.87%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0095] Example 7 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 1, except that PAE-1-1 in Example 1 is replaced by PAE-1-7, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Example 7 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.86, photolithography resolution is 4.6µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.3, dielectric loss factor is 0.0043, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.76%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0096] Example 8 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 1, except that PAE-1-1 in Example 1 is replaced by PAE-1-8, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Example 8 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.89, photolithography resolution is 4.5µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.2, dielectric loss factor is 0.0037, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.69%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0097] Example 9 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 1, except that PAE-1-1 in Example 1 is replaced by PAE-1-9, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Example 9 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.91, photolithography resolution is 4.3µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.3, dielectric loss factor is 0.0038, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.76%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0098] Example 10 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 1, except that PAE-1-1 in Example 1 is replaced by PAE-1-10, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Example 10 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.86, photolithography resolution is 4.4µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.4, dielectric loss factor is 0.0037, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.68%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: many microcracks or defects were observed, rated as "poor"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 8 / 100, rated as "good"; ⑥ Comprehensive performance evaluation: one indicator is poor, rated as "poor".
[0099] Comparative Example 3 The preparation method of the positive photosensitive polyimide resin solution is the same as that in Example 8, except that PAE-2-1 in Example 8 is removed, and all other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Comparative Example 3 was evaluated using the above performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.88, photolithography resolution is 4.6µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.4, dielectric loss factor is 0.0120, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.76%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 8 / 100, rated as "good"; ⑥ Comprehensive performance evaluation: one indicator is poor, rated as "poor".
[0100] By comparing the weight ratio of the first phenolic hydroxyl polyaminate resin series (PAE-1) and the second phenolic hydroxyl polyaminate resin (PAE-2-1) in Examples 7 to 11 of 1:1, the influence of the different molecular structures of the phenolic hydroxyl aromatic dianhydride monomers (4HFAP, 3HFHA, 4HFHA) of the PAE-1 series resins (PAE-1-6, PAE-1-7, PAE-1-8, PAE-1-9) on the overall performance of the prepared positive photosensitive resin was investigated. Based on the performance evaluation results of the positive photosensitive polyimide resin solutions from Examples 7 to 11 and Comparative Example 3, it can be seen that the positive photosensitive polyimide resin solution formed by fully mixing the mixed resin of PAE-1-6 or PAE-1-7, PAE-1-8, PAE-1-9 and PAE-2-1 in a 1:1 weight ratio with other components such as photoacidifier, thermal crosslinking agent, thermal acidifier, and tackifier has excellent comprehensive performance, and its comprehensive performance evaluation is "excellent". However, the positive photosensitive polyimide resin solution prepared by combining the mixed resin of PAE-1-10 and PAE-2-1 in a 1:1 weight ratio has a comprehensive performance evaluation of "poor". In comparison, when the phenolic hydroxyl polyaminate resin (PAE-1-8) is only a single component and does not form a mixed resin with PAE-2-1, the comprehensive performance evaluation of the prepared positive photosensitive polyimide resin solution is "poor".
[0101] Example 11 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 2, except that PAE-2-1 in Example 2 is replaced by PAE-2-2, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Example 11 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.86, photolithography resolution is 4.6µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.3, dielectric loss factor is 0.0046, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.76%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0102] Example 12 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 2, except that PAE-2-1 in Example 2 is replaced by PAE-2-3, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Example 12 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.89, photolithography resolution is 4.7µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.2, dielectric loss d-factor is 0.0037, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.67%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0103] Example 13 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 2, except that PAE-2-1 in Example 2 is replaced by PAE-2-4, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Example 13 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.88, photolithography resolution is 4.4µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.3, dielectric loss factor is 0.0038, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.72%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0104] Example 14 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 2, except that PAE-2-1 in Example 2 is replaced by PAE-2-5, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Example 14 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.88, photolithography resolution is 4.3µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.3, dielectric loss factor is 0.0037, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.74%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0105] Example 15 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 2, except that PAE-2-1 in Example 2 is replaced by PAE-2-6, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Example 15 was evaluated using the above-mentioned performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.86, photolithography resolution is 4.6µm, rated as "excellent"; ② High frequency and low dielectric loss: dielectric constant is 3.4, dielectric loss factor is 0.0042, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.73%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: no microcracks or defects were observed, rated as "excellent"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: all indicators are excellent, rated as "excellent".
[0106] Comparative Example 4 The preparation method of the positive photosensitive polyimide resin solution is carried out according to the preparation method of Example 13, except that PAE-1-2 in Example 13 is removed, and the other steps are the same, to obtain the positive photosensitive polyimide resin solution. The performance of the positive photosensitive polyimide resin liquid of Comparative Example 4 was evaluated using the above performance evaluation method. The evaluation results are as follows: ① Photolithography processability: steepness is 0.88, photolithography resolution is 10.3µm, rated as "poor"; ② High frequency and low dielectric loss: dielectric constant is 3.4, dielectric loss factor is 0.0045, rated as "excellent"; ③ Chemical corrosion resistance: film thickness change rate is 0.77%, no microcracks or defects were observed, rated as "excellent"; ④ Damp heat resistance: a small number of microcracks or defects were observed, rated as "good"; ⑤ Adhesion to copper surface: cross-cut adhesion test result is 0 / 100, rated as "excellent"; ⑥ Comprehensive performance evaluation: one indicator is poor, rated as "poor".
[0107] By comparing the weight ratio of the first phenolic hydroxyl polyaminate resin (PAE-1-2) and the second phenolic hydroxyl polyaminate resin series (PAE-2) in Examples 2 and 11-15 (PAE-2 series resin) at 1:1, the influence of the different molecular structures of aromatic tetracarboxylic dianhydrides (33-ODPA, 34-ODPA, 44-ODPA and their 1:1 weight mixtures) on the overall performance of the prepared positive photosensitive resin was investigated. The results showed that the mixed resin formed by thoroughly mixing PAE-2-1, 2-2, 2-3, PAE-2-4, PAE-2-5, PAE-2-6 with PAE-1-2 at a 1:1 weight ratio, along with other components such as photoacid-producing agents, thermal crosslinking agents, and tackifiers, resulted in a positive photosensitive polyimide resin solution with excellent overall performance, rated as "excellent". In comparison, when the phenolic hydroxyl polyamide resin (PAE-2-3) is only a single component, rather than a mixed resin formed with PAE-1-2, the overall performance evaluation of the prepared positive photosensitive polyimide resin solution is "poor".
[0108] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A positive photosensitive polyimide resin adhesive, characterized in that, It is obtained by mixing the following components: 100 parts of polyamic acid ester resin, 3 to 40 parts of photoacid generator, 3 to 40 parts of thermal crosslinking agent, 0.1 to 20 parts of thermal acid generator, 3 to 40 parts of sensitizer, 3 to 40 parts of tackifier and organic solvent; The solid content of the positive photosensitive polyimide resin solution is 15wt.%~45wt.%, and the viscosity at room temperature is 500mPa.s~4000mPa.s; The polyamic acid ester resin is obtained by mixing a first phenolic hydroxyl polyamic acid ester resin and a second phenolic hydroxyl polyamic acid ester resin; the first phenolic hydroxyl polyamic acid ester resin accounts for 50% to 99% of the mass percentage of the polyamic acid ester resin; the main chain structure of the first phenolic hydroxyl polyamic acid ester resin includes ester aliphatic segments or ester aromatic ring segments.
2. The positive photosensitive polyimide resin adhesive according to claim 1, characterized in that, The general structural formula of the first phenolic hydroxyl polyamide ester resin is as follows: Where m = 2 to 50; X1 is selected from one of the following structural formulas: Where n = 1 to 3; Y1 is selected from one of the following structural formulas: ; R1 is a straight-chain alkane containing C1 to C8 atoms; E1 is a capping group.
3. The positive photosensitive polyimide resin liquid according to claim 1, characterized in that, The general structural formula of the second phenolic hydroxyl polyamide ester resin is as follows: Where m' = 2 to 50; X2 is selected from one of the following general structural formulas: ; Y2 is selected from one of the following general structural formulas: ; R2 is a straight-chain alkane containing C1 to C8; E2 is a capping group.
4. The positive photosensitive polyimide resin adhesive according to claim 1, characterized in that, The first phenolic hydroxyl polyamic acid ester resin is prepared by the following method: An esterification reaction is carried out between a first aromatic dianhydride containing an ester-based aliphatic chain segment or an ester-based aromatic ring segment and a first fatty alcohol in a reaction solvent to generate a first aromatic diacid diester; the first aromatic diacid diester is then subjected to an acyl chloride reaction with thionyl chloride to generate a first aromatic diester diacyl chloride; The first aromatic diester diacyl chloride and the first phenolic hydroxyl-containing aromatic diamine are subjected to a polycondensation reaction in a reaction solvent. Then, a reactive end-capping agent and a disiloxane-based silane coupling agent are added, and the reaction is continued to generate a first phenolic hydroxyl-containing polyamic acid ester resin solution. After precipitation and separation in a poor solvent, the first phenolic hydroxyl-containing polyamic acid ester resin is obtained. The molar ratio of the first aromatic dianhydride, the first fatty alcohol, and thionyl chloride is 1:2 to 2.1:2 to 2.1; The molar ratio of the first aromatic dianhydride to the first phenolic hydroxyl-containing aromatic diamine is 1:0.9-1; The first phenolic hydroxyl polyamide ester resin has a GPC molecular weight of 1×10⁻⁶. 4 Up to 3×10 4 ; The first aromatic dianhydride is at least one of ethylene glycol dimethacrylate, butylene glycol dimethacrylate, hexanediol dimethacrylate, resorcinol dimethacrylate, and hydroquinone dimethacrylate.
5. The positive photosensitive polyimide resin adhesive according to claim 1, characterized in that, The second phenolic hydroxyl-containing polyamic acid ester resin is prepared by the following method: The second aromatic dianhydride is esterified with the second fatty alcohol in a reaction solvent to generate the second aromatic diacid diester; the second aromatic diacid diester is then acyl-chlorinated with thionyl chloride to generate the second aromatic diester diacyl chloride. The second aromatic diester diacyl chloride and the second phenolic hydroxyl-containing aromatic diamine are subjected to a polycondensation reaction in a reaction solvent. Then, a reactive end-capping agent and a disiloxane-based silane coupling agent are added, and the reaction is continued to generate a second phenolic hydroxyl-containing polyamic acid ester resin solution. After precipitation and separation in a poor solvent, the second phenolic hydroxyl-containing polyamic acid ester resin is obtained. The molar ratio of the second aromatic dianhydride, the second fatty alcohol, and thionyl chloride is 1:2 to 2.1:2 to 2.
1. The molar ratio of the second aromatic dianhydride to the second phenolic hydroxyl-containing aromatic diamine is 1:0.9-1; The second phenolic hydroxyl polyamide ester resin has a GPC molecular weight of 1×10⁻⁶. 4 Up to 3×10 4 ; The second aromatic dianhydride is at least one of 2,3,2',3'-diphenyl ether tetracarboxylic dianhydride, 2,3',3,4'-diphenyl ether tetracarboxylic dianhydride, and 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride.
6. The positive photosensitive polyimide resin adhesive according to claim 4 or 5, characterized in that, The first phenolic hydroxyl-containing aromatic diamine and the second phenolic hydroxyl-containing aromatic diamine are each selected from at least one of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, 2,2-bis(4-amino-3-hydroxyphenyl)hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)propane, bis(4-amino-3-hydroxyphenyl)methane, 2,2'-bis[N-(3-aminobenzoamido)-3-amino-4-hydroxyphenyl]hexafluoropropane and 2,2'-bis[N-(4-aminobenzoamide)-3-amino-4-hydroxyphenyl]hexafluoropropane.
7. The positive photosensitive polyimide resin adhesive according to claim 4 or 5, characterized in that, Reactive end-capping agents include maleic anhydride, 4-aminobenzocyclobutene, 4-vinylaniline, norbornene, allylamine, 4-ethynylphthalic anhydride, 4-phenylethynylphthalic anhydride, 4-ethynylaniline, 3-ethynylaniline, 3-phenylethynylaniline, 4-phenylethynylaniline, 4-(4-aminophenylethynyl)phenylacetylene, 4-[(trimethylsilyl)-ethynyl]aniline, and 4-(4-amino-phenyl-... At least one of (E)-2-methyl-but-3-yn-2-ol, (E)-3-aminocinnamic acid, and propargylamine; the disiloxane silane coupling agent is at least one of 1,3-bis(3-aminopropyl)tetramethyldisiloxane, 1,3-bis(3-aminopropyl)tetraphenyldisiloxane, 1,3-bis(3-aminophenoxy)tetramethyldisiloxane, and 1,3-bis(4-aminophenoxy)tetramethyldisiloxane.
8. The positive photosensitive polyimide resin liquid according to claim 1, characterized in that, Photoacid-producing agents are diazonoquinone compounds, iodonium salts, or sulfonium salts; Thermal crosslinking agents are compounds containing epoxy groups, or compounds containing hydroxymethyl or alkoxymethyl groups; The thermally induced acid-producing agent is an alkyl sulfonic acid, a perfluoroalkyl sulfonic acid, or a pyridinium salt of an alkyl sulfonic acid, an alkylpyridinium salt, a diaryl iodine salt, a di(alkylaryl)iodine salt, a trialkyl sulfonium salt, a dialkyl monoaryl sulfonium salt, or a diaryl monoalkyl iodine salt or an ester compound, including at least one of p-toluenesulfonic acid pyridinium salt, di(tert-butylphenyl)iodine salt of p-toluenesulfonic acid, trimethyl sulfonium salt of trifluorobenzenesulfonic acid, diphenylmethyl sulfonium salt of trifluoromethanesulfonic acid, and p-toluenesulfonic acid-2-methoxyethyl ester; Sensitizers are compounds containing phenolic hydroxyl, hydroxyl, or carboxyl groups.
9. A method for preparing a positive photosensitive polyimide resin liquid according to any one of claims 1 to 8, characterized in that, Includes the following steps: A first phenolic hydroxyl polyamide ester resin, a second phenolic hydroxyl polyamide ester resin, a photoacid-generating agent, a thermal crosslinking agent, a thermal acid-generating agent, a sensitizer, and a tackifier are dissolved in an organic solvent under stirring to form a homogeneous solution, thereby obtaining a positive photosensitive polyimide resin solution. The solid content of the positive photosensitive polyimide resin solution is 15wt.% to 45wt.%, and the viscosity at room temperature is 500mPa.s to 4000mPa.s.
Citation Information
Patent Citations
High-frequency low-dielectric-loss poly (aryl ester-imide) film as well as preparation method and application thereof
CN116655911A
Cured film formed by curing photosensitive resin composition and method for manufacturing same
US10545406B2
Positive-type photosensitive resin composition, method for producing resist pattern, semiconductor device, and electronic device
US8461699B2